Keragaman Daerah Kontrol DNA Mitokondria Rusa Timor (Cervus timorensis timorensis) di Pulau Timor, Alor, dan Pantar - M. Syamsul Zein (Biota : Jurnal Ilmiah Ilmu-Ilmu Hayati, 2007)
A study on mtDNA control region diversity of the timor deer was conducted in EastNusa Tenggara Province. Sample consisted of 20 individuals from 3 islands (Timor,Pantar, and Alor). Total DNA were extracted from leucocyte (buffy coat). Fragmentcontrol region of the mitochondrial DNA were amplified by Polymerase ChainReaction (PCR) using primers of forward primer5”AAACCAGAAAAGGAGAGCAAC3” and reverse primer5”TCATCTAGGCATTTTCAGTGCC3”. Nucleotide sequence of the mitochondrialcontrol region were aligned by using ClastalX and phylogenetic analyses by Neighbor-Joining methode. Kimura two-parameter model of nucleotide substitution usingpairwise distance calculation program was implemented with the Mega softwareversion 3. The purposes of this study, were to examine the control region (D-Loop) ofthe mitochondrial DNA and to discuss the phylogeography of the Cervus timorensistimorensis in East Nusa Tenggara Province. Results indicated that from 435 basenucleotide sequences, 16 polymorphic sites with 8 haplotypes were found among 3islands. Haplotype diversity and nucleotide diversity were 0.056 and 0.039. DNAdistances values ranged from 0.014 to 0.021.